M2 monthly and annual mode-1 and mode-2 internal tide atlases from altimetry data and MIOST: focus on the Indo-Philippine archipelago and the region off the Amazon shelf - M. Tchilibou; S. Barbot; L. Carrere; A. Koch-Larrouy; G. Dibarboure; C. Ubelmann (Ocean Science, 2025)
The M2 MIOST24 (Multivariate Inversion of Ocean Surface Topography 2024) internal tide atlases described in this study are available in annual (MIOST24a) and monthly (MIOST24m) regional versions for modes 1 and 2 in the Indo-Philippine archipelago and the region off the Amazon shelf. They are derived from 25 years (1993–2017, period 1) of sea level anomalies (SLAs) from altimetry observations. Compared to the MIOST22 (Multivariate Inversion of Ocean Surface Topography 2022) internal tide atlases, MIOST24 incorporates M2 mode-1 and mode-2 wavelengths based on monthly stratification profiles from GLORYS12v1 (1993–2020). The differences between MIOST24a and MIOST22a lead to a RMSD (root mean square difference) of up to 3 cm, reflecting amplitude changes, while the RMSD between MIOST24a and the internal tide atlas HRET (High-Resolution Empirical Tide) indicates both amplitude and phase differences. MIOST24m highlights significant monthly variability of M2 internal tides in the Indo-Philippine archipelago and off the Amazon shelf. In the Amazon region, the internal tide propagates far offshore from March to June but is blocked closer to the coast from August to December. In both regions, the RMSDs between the MIOST24a annual and MIOST24m monthly mode-1 atlases are mainly governed by the phase contribution term. This suggests that the monthly variability of the mode-1 internal tide is more affected by changes in its propagation direction than by fluctuations in amplitude. In contrast, for mode 2, the monthly variability is predominantly associated with amplitude variations, particularly near internal tide generation sites. Variance reductions of SLAs show that MIOST24m outperforms MIOST24a, MIOST22a, and HRET in period 1 in the two regions of interest and in the Amazon region in period 2 (2018–2023). Monthly atlases are therefore recommended to correct the internal tides of the SLAs used to derive them. All these results support the development of MIOST24 global atlases.